Virtual reality and artificial intelligence: Co-creation process between consumers and firms in an area of smart cities - Ferreira, M. M.; Loureiro, S. M. C.; Pereira, H. (Augmented reality and virtual reality: New trends in immersive technology, Conference Proceedings, 2021)
The aim of this study is twofold: provide an overview of the virtual reality and artificial intelligence conceptualization and applications and propose a framework of consumer -firm experience process in the context of smart cities. The framework will give a novel perspective on the topic and provide theoretical and contributions.